NAVAL PRESENCE AND STRATEGIC COMPETITION BETWEEN INDIA AND CHINA IN THE INDIAN OCEAN REGION FROM THE EARLY 21ST CENTURY TO THE PRESENT - Vo, Minh Tap; Nguyen, Que Son; Tran, Xuan Hiep (VNU Journal of Foreign Studies, 2025)
The Indian Ocean Region (IOR) plays an increasingly important geopolitical and geostrategic role for the world in the 21st century, especially large countries such as the U.S., India, France, Japan and China. India has maintained a much stronger naval presence than China in the IOR for decades, but the balance is starting to shift. Since 2008, China has significantly increased its naval presence in the IOR, raising Indian concerns about the possibility of military encirclement and raising questions in strategic thinking about China's ultimate goals. The article focuses on analyzing the interests and naval presence of India and China and the naval power competition between the two countries in the IOR, along with the impacts of the above issue on each country and region.